Parkinson's disease alters multisensory perception: Insights from the Rubber Hand Illusion. (March 2017) - Ding, Catherine; Palmer, Colin J.; Hohwy, Jakob; Youssef, George J.; Paton, Bryan; Tsuchiya, Naotsugu; Stout, Julie C.; Thyagarajan, Dominic
Abstract: Background: Manipulation of multisensory integration induces illusory perceptions of body ownership. Patients with Parkinson's disease (PD), a neurodegenerative disorder characterised by striatal dopamine deficiency, are prone to illusions and hallucinations and have sensory deficits. Dopaminergic treatment also aggravates hallucinations in PD. Whether multisensory integration in body ownership is altered by PD is unexplored. Objective: To study the effect of dopamine neurotransmission on illusory perceptions of body ownership. Methods: We studied the Rubber Hand Illusion (RHI) in 21 PD patients (on- and off-medication) and 21 controls. In this experimental paradigm, synchronous stroking of a rubber hand and the subject's hidden real hand results in the illusory experience of 'feeling' the rubber hand, and proprioceptive mislocalisation of the real hand towards the rubber hand ('proprioceptive drift'). Asynchronous stroking typically attenuates the RHI. Results: The effect of PD on illusory experience depended on the stroking condition ( b = −2.15, 95% CI [−3.06, −1.25], p < .0001): patients scored questionnaire items eliciting the RHI experience higher than controls in the illusion-attenuating (asynchronous) condition, but not in the illusion-promoting (synchronous) condition. PD, independent of stroking condition, predicted greater proprioceptive drift ( b = 15.05, 95% CI [6.05, 24.05], p = .0022); the longer the disease duration, the greater the proprioceptive drift. However, the RHI did not affect subsequent reaching actions. On-medication patients scored both illusion (critical) and mock (control) questionnaire items higher than when off-medication, an effect that increased with disease severity (log ( OR ) =.014, 95% CI [.01, .02], p < .0001). Conclusion: PD affects illusory perceptions of body ownership in situations that do not typically induce them, implicating dopamine deficit and consequent alterations in cortico-basal ganglia-thalamic circuitry in multisensory integration. Dopaminergic treatment appears to increase suggestibility generally rather than having a specific effect on own-body illusions, a novel finding with clinical and research implications. Highlights: Parkinson's disease affects own-body perception in the Rubber Hand Illusion (RHI). Patients do not reject RHI as strongly as controls after asynchronous stroking. RHI strength is similar between patients and controls after synchronous stroking. Parkinson's disease increases proprioceptive drift independent of stroking. Dopaminergic drugs increased agreement with questionnaire items non-discriminately.